Geochronology of sediment cores from the Vefsnfjord, Norway. (September 2021) - Heldal, H.E.; Helvik, L.; Appleby, P.; Haanes, H.; Volynkin, A.; Jensen, H.; Lepland, A.
Abstract: The sedimentary environment is a repository and carrier for a variety of pollutants, and sediment transport from land to coastal areas is an important environmental process. In the present study, we use 210 Pb/ 226 Ra and 137 Cs in sediment cores to assess sediment supply rates at four sites within the Vefsnfjord in Nordland county, Norway. This area was highly affected by fallout from the Chernobyl accident in 1986 and inventories of 137 Cs in the fjord are much higher than in many other Norwegian fjords. Sedimentation rates between 0.042 and 0.25 g cm −2 y −1 (0.060 and 0.38 cm y −1 ) were determined using a combination of the Constant Rate of Supply (CRS) and Constant Flux:Constant Sedimentation rate (CF:CS) models. Well-defined 137 Cs concentration peaks were used as a supplementary tool to the 210 Pb dating methods. Highlights: Sedimentation rates in Vefsnfjord were determined using 210 Pb and 226 Ra Dates were calculated using the CRS and CF:CS models Corrections were made using chronostratigraphic dates determined from 137 Cs records Sedimentation rates at the outer fjord site have increased significantly since 1986 Sedimentation rates were relatively constant at two of the three inner fjord sites